Corrosion-resistant coating and preparation method thereof
By using tea polyphenol-modified graphene composite materials in the coating, the problem of easy aggregation and poor compatibility in the coating is solved, and the corrosion resistance and durability of the coating are significantly improved.
Patent Information
- Application Number
- CN202411535661.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing epoxy resin anti-corrosion coatings have insufficient corrosion resistance and durability during long-term use, and graphene is prone to aggregation in the coating as a filler, and have poor compatibility, resulting in poor corrosion resistance.
Tea polyphenol-modified graphene composite material is used to form ammonium carboxylate by reacting urea with carboxyl groups on the surface of graphene to enhance the dispersion of graphene, and the antioxidant effect of tea polyphenols is used to synergize the corrosion resistance of the paint.
It improves the coating's water absorption rate, strong adhesion, acid resistance, alkali resistance, salt spray resistance and corrosion resistance on metal surfaces, and significantly improves the durability and performance stability of long-term use.
Smart Images

Figure BDA0005111480070000081 
Figure BDA0005111480070000091 
Figure BDA0005111480070000092
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, and in particular to a corrosion-resistant coating and a preparation method thereof. Background Art
[0002] Epoxy anti-corrosion coatings are widely recognized for their excellent effectiveness in protecting metal equipment, offshore facilities and civil engineering structures from corrosion. Their advantages lie in excellent blocking and shielding properties, high efficiency, easy application and cost-effectiveness. However, the long-term corrosion resistance and durability of such coating samples may be affected due to the presence of brittleness and micropores formed during solvent evaporation.
[0003] For example, CN113831825A discloses a self-repairing waterborne polyurethane anticorrosive coating and its preparation method, wherein the coating comprises, by weight: 0.002-0.005 parts of graphene oxide, 20-50 parts of waterborne polyurethane emulsion, 5-20 parts of tung oil, 5-15 parts of polyvinyl alcohol, 1-10 parts of silane coupling agent, 1-10 parts of phosphoric acid, 0.01-0.4 parts of photoinitiator and 30-110 parts of deionized water. The application uses an appropriate amount of graphene oxide to improve the water resistance, corrosion resistance, and mechanical properties of polyvinyl alcohol.
[0004] For example, CN118562380A discloses an outdoor steel structure anti-corrosion coating and a preparation method thereof, comprising component A and component B. Component A consists of the following components, by weight: 35-55 parts of aqueous polyurethane emulsion, 0.1-0.5 parts of anti-precipitation agent, 0.5-1 parts of dispersant, 0.1-0.5 parts of defoaming agent, 1-3 parts of preservative, and 1-5 parts of leveling agent; component B consists of the following components: 40-50 parts of composite modified resin emulsion, 0.5-2 parts of polyvinyl acetate, and 1-5 parts of boron nitride nanosheet-graphene composite material. The nitrile rubber, vinyl polyester resin and n-propanol are mixed, hydrochloric acid is added dropwise, and then the temperature is raised to 65-75°C for reaction, and then a capping agent, pentaerythritol stearate, and vinyl acetate-ethylene copolymer are added, and a capping reaction is carried out at 60-80°C, and an initiator and carbon nanotubes with a tube length of 150-300 μm are added and mixed, and then the solvent is removed by reduced pressure distillation, and deionized water is added for emulsification to obtain the composite modified resin emulsion. Boron nitride nanosheet-graphene composite material is used to achieve the purpose of corrosion resistance.
[0005] However, although graphene as a filler can improve the corrosion resistance of the coating, it is easy to aggregate on a large scale in the coating, which weakens the performance, and its compatibility with solvents or polymers is poor, resulting in no obvious improvement in corrosion resistance. In view of this, the present invention is specially proposed. Summary of the invention
[0006] The purpose of the present invention is to provide a corrosion-resistant coating and a preparation method thereof in order to overcome the defects of the above-mentioned prior art. The coating obtained by the present invention has the characteristics of low water absorption, strong adhesion, acid resistance, alkali resistance, salt spray resistance and excellent corrosion resistance when used for metal coating.
[0007] The purpose of the present invention can be achieved by the following technical solutions:
[0008] The present invention provides a corrosion-resistant coating, comprising a component A and a component B;
[0009] In parts by weight, component A includes 40-60 parts of epoxy resin, 20-40 parts of pigments and fillers, 1-5 parts of additives, and 10-50 parts of deionized water; component B includes 40-60 parts of water-based curing agent, 1-5 parts of tea polyphenol-modified graphene composite material, and 30-50 parts of deionized water;
[0010] The mass ratio of component A to component B is (4-7):1.
[0011] Preferably, the tea polyphenol-modified graphene composite material is prepared by the following method:
[0012] S1. Dissolve graphene in water, perform ultrasonic treatment for 1-2h until the graphene is evenly dispersed in the water, then add urea, the mass ratio of urea to graphene is 4-6:1, stir and reflux at 60-100°C for 0.5-1.5h, wash and dry to obtain a modified graphene material;
[0013] S2, dissolving tea polyphenols in an organic solvent, then adding the modified graphene material in S1, stirring for 1-3 hours, centrifuging, washing, and freeze-drying to obtain a tea polyphenol-modified graphene composite material.
[0014] Preferably, the epoxy value of the epoxy resin is 450-550 mol / 100 g, the pH value is 7.5-8.5, the solid content is 50-55%, and the particle size is 0.8-1.0 μm;
[0015] And / or, the pigments and fillers are selected from one or more of titanium dioxide, talc, feldspar powder, precipitated barium sulfate, and mica powder;
[0016] And / or, the water-based curing agent is a water-based epoxyamine curing agent.
[0017] Preferably, the auxiliary agent includes 0.5-1.5 parts of dispersant, 0.1-1 parts of defoamer, 0.1-1 parts of preservative, and 0.1-1 parts of leveling agent.
[0018] Preferably, the dispersant is one or more of polycarboxylic acid sodium salt, polyacrylate potassium salt, and polyacrylate sodium salt;
[0019] And / or, the defoamer is a higher alcohol defoamer or an organosilicon defoamer;
[0020] And / or, the preservative is one or more of aluminum dihydrogen tripolyphosphate, zinc phosphate, and zinc hydroxyphosphite;
[0021] And / or, the leveling agent is a polyether siloxane copolymer.
[0022] The present invention also provides a method for preparing a corrosion-resistant coating, comprising the following steps:
[0023] Stir component A thoroughly and uniformly, then stir component B thoroughly and uniformly and heat to 50-80°C, preferably 60°C, and then mix and stir component A and component B until cooled to room temperature, wherein the mass ratio of component A to component B is 4-7:1;
[0024] Among them, component A includes 40-60 parts of epoxy resin, 20-40 parts of pigments and fillers, 1-5 parts of additives, and 10-50 parts of deionized water; component B includes 40-60 parts of water-based curing agent, 1-5 parts of tea polyphenol-modified graphene composite material, and 30-50 parts of deionized water.
[0025] Preferably, the tea polyphenol-modified graphene composite material is prepared by the following method:
[0026] S1. Dissolve graphene in water, perform ultrasonic treatment for 1-2h until the graphene is evenly dispersed in the water, then add urea, the mass ratio of urea to graphene is 4-6:1, stir and reflux at 60-100°C for 0.5-1.5h, wash and dry to obtain a modified graphene material.
[0027] S2, dissolving tea polyphenols in an organic solvent, then adding the modified graphene material in S1, stirring for 1-3 hours, centrifuging, washing, and freeze-drying to obtain a tea polyphenol-modified graphene composite material.
[0028] Preferably, the epoxy value of the epoxy resin is 450-550 mol / 100 g, the pH value is 7.5-8.5, the solid content is 50-55%, and the particle size is 0.8-1.0 μm;
[0029] And / or, the pigments and fillers are selected from one or more of titanium dioxide, talc, feldspar powder, precipitated barium sulfate, and mica powder;
[0030] And / or, the water-based curing agent is a water-based epoxyamine curing agent;
[0031] And / or, the auxiliary agent includes 0.5-1.5 parts of dispersant, 0.1-1 parts of defoamer, 0.1-1 parts of preservative, and 0.1-1 parts of leveling agent.
[0032] The present invention further provides a corrosion-resistant coating obtained by the above-mentioned method for preparing the corrosion-resistant coating.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] In order to enhance the compatibility of graphene and solvent or polymer, the present invention adopts a covalent energy grouping method. The graphene surface has various energy groups, such as hydroxyl and epoxy groups distributed on the base plane, and carboxyl and carbonyl groups located at the edge sites. The amino groups of urea are used to react with the carboxyl groups distributed on the graphene surface to form ammonium carboxylate. Thus, the amino groups are successfully grafted onto the graphene, so that the surface of the graphene becomes looser and rougher, so that the graphene is more dispersed in the organic coating and the possibility of agglomeration is reduced, thereby improving the corrosion resistance of the coating.
[0035] In addition, tea polyphenols themselves have the function of free radical scavenger, but simply adding tea polyphenols to the paint will cause its agglomeration. The uneven distribution cannot prevent the natural weathering and degradation of the paint. The tea polyphenol molecules contain multiple phenolic hydroxyl groups, which can form hydrogen bonds with the carboxyl groups on the surface of graphene to further enhance the dispersion ability of graphene. Conversely, the antioxidant effect of tea polyphenols prevents the natural weathering and oxidation of the paint, and further prevents the entry of corrosive media. The synergistic effect of the two improves the corrosion resistance of the paint. DETAILED DESCRIPTION
[0036] For ease of understanding of the present application, the present application will be described more fully below by way of embodiments. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.
[0037] For simplicity, the present application only explicitly discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an unclearly recorded range; and any lower limit can be combined with other lower limits to form an unclearly recorded range, and any upper limit can be combined with any other upper limit to form an unclearly recorded range. In addition, although not clearly recorded, each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unclearly recorded range.
[0038] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present application. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. It should be noted that, unless otherwise stated, the term "and / or" used herein includes any and all combinations of one or more related listed items, and "above", "below" include the number, and the meaning of "multiple" in "one or more" is more than two.
[0039] Due to the brittleness and micropores formed during the solvent evaporation process of epoxy resin anti-corrosion coatings, the long-term corrosion resistance and durability of such coating samples may be affected. The compatibility of graphene alone with the coating is insufficient, resulting in reduced corrosion resistance.
[0040] In view of this, the first aspect of the embodiment of the present application provides a corrosion-resistant coating, which includes component A and component B. In parts by weight, component A includes 40-60 parts of epoxy resin, 20-40 parts of pigments and fillers, 1-5 parts of additives, and 10-50 parts of deionized water; component B includes 40-60 parts of water-based curing agent, 1-5 parts of tea polyphenol-modified graphene composite materials, and 30-50 parts of deionized water; wherein the mass ratio of component A to component B is (4-7):1, preferably 6:1.
[0041] In an optional embodiment, the tea polyphenol-modified graphene composite material is prepared by the following method:
[0042] S1. Dissolve graphene in water, then perform ultrasound, the ultrasound time is 1-2h, preferably 1.5h, until the graphene is evenly dispersed in the water, then add urea thereto, wherein the mass ratio of urea to graphene is 4-6:1, preferably 5:1, stir the obtained liquid phase and reflux at 60-100°C for 0.5-1.5h, preferably reflux at 80°C for 1h, finally wash the mixture with deionized water for multiple times, and dry it in a vacuum oven overnight to obtain a modified graphene material.
[0043] S2, dissolving tea polyphenols in an organic solvent, preferably ethanol, then adding the modified graphene material in S1, stirring for 1-3 hours, preferably 2 hours, then high-speed centrifuging, washing with deionized water, and freeze-drying to obtain a tea polyphenol-modified graphene composite material.
[0044] In the present application, in order to enhance the compatibility of graphene and solvents or polymers, a covalent energy grouping method is adopted. In fact, there are various energy groups on the surface of graphene, such as hydroxyl and epoxy groups distributed on the base plane, and carboxyl and carbonyl groups located at the edge sites. The amino groups of urea are reacted with the carboxyl groups distributed on the surface of graphene to form ammonium carboxylates. Thus, the amino groups are successfully grafted onto the graphene, making the surface of the graphene looser and rougher, making the graphene more dispersed in the organic coating and reducing the possibility of agglomeration, thereby improving the corrosion resistance of the coating.
[0045] In addition, tea polyphenols themselves have the function of free radical scavenger, but simply adding tea polyphenols to the paint will cause its agglomeration. The uneven distribution cannot prevent the natural weathering and degradation of the paint. The tea polyphenol molecules contain multiple phenolic hydroxyl groups, which can form hydrogen bonds with the carboxyl groups on the surface of graphene to further enhance the dispersion ability of graphene. Conversely, the antioxidant effect of tea polyphenols prevents the natural weathering and oxidation of the paint, and further prevents the entry of corrosive media. The synergistic effect of the two improves the corrosion resistance of the paint.
[0046] In an optional embodiment, the epoxy resin is an aqueous epoxy resin dispersion. In essence, the epoxy resin is prepared by a non-ionic emulsifier through a phase inversion method and has good stability, low viscosity, and fine emulsion particles.
[0047] In an optional embodiment, the epoxy resin is an aqueous epoxy emulsion with a main chain segment grafted with a multi-secondary amino group, wherein the secondary amino group can react with the isocyanate in the topcoat (polyurethane coating) component before the epoxy group in the epoxy primer to form polyurea, which can reduce the occurrence of side reactions in the wet-to-wet contact between the primer and topcoat while forming a uniform and dense coating with the topcoat, thereby improving the appearance and performance of the matching paint film.
[0048] In an optional embodiment, the epoxy value of the epoxy resin is 450-550 mol / 100 g, the pH value is 7.5-8.5, the solid content is 50-55%, and the particle size is 0.8-1.0 μm.
[0049] In an optional embodiment, the epoxy resin is selected from epoxy resins of model XS0402 (with grafted polyamine groups) and XS0402 CI (without grafted polyamine groups) provided by Honghui Company, or epoxy resins of model EPIKOTE TM One or more of the epoxy resins of Resin 6529.
[0050] In an optional embodiment, the pigment filler is selected from one or more of titanium dioxide, talc, feldspar powder, precipitated barium sulfate, and mica powder.
[0051] In an optional embodiment, the auxiliary agent includes one or more of a dispersant, a defoamer, a preservative, a leveling agent, a rheological agent, and an anti-flash rust agent; in particular, by weight, the auxiliary agent preferably includes 0.5-1.5 parts of a dispersant, 0.1-1 parts of a defoamer, 0.1-1 parts of a preservative, and 0.1-1 parts of a leveling agent.
[0052] In an optional embodiment, the dispersant is one or more of polycarboxylic acid sodium salt, polyacrylate potassium salt, and polyacrylate sodium salt.
[0053] In an optional embodiment, the defoaming agent is a high-carbon alcohol defoaming agent or a silicone defoaming agent.
[0054] In an optional embodiment, the preservative is one or more of aluminum dihydrogen tripolyphosphate, zinc phosphate, and zinc hydroxyphosphite.
[0055] In an optional embodiment, the leveling agent is a polyether siloxane copolymer.
[0056] In an optional embodiment, the water-based curing agent is a water-based epoxyamine curing agent, with an active hydrogen equivalent of 140 g / mol (solid basis) and a solid content of 80%. Preferably, the water-based epoxyamine curing agent is an aqueous solution of a polyamide-modified alicyclic polyamine adduct.
[0057] A second aspect of the present application provides a method for preparing a corrosion-resistant coating, comprising the following steps:
[0058] Stir component A thoroughly and evenly, then stir component B thoroughly and evenly and heat to 50-80°C, preferably 60°C, then mix and stir components A and B until cooled to room temperature, wherein the mass ratio of component A to component B is 4-7:1, preferably 6:1.
[0059] Among them, component A includes 40-60 parts of epoxy resin, 20-40 parts of pigments and fillers, 1-5 parts of additives, and 10-50 parts of deionized water; component B includes 40-60 parts of water-based curing agent, 1-5 parts of tea polyphenol-modified graphene composite material, and 30-50 parts of deionized water.
[0060] In an optional embodiment, the tea polyphenol-modified graphene composite material is prepared by the following method:
[0061] S1. Dissolve graphene in water, then perform ultrasound, the ultrasound time is 1-2h, preferably 1.5h, until the graphene is evenly dispersed in the water, then add urea thereto, wherein the mass ratio of urea to graphene is 4-6:1, preferably 5:1, stir the obtained liquid phase and reflux at 60-100°C for 0.5-1.5h, preferably reflux at 80°C for 1h, finally wash the mixture with deionized water for multiple times, and dry it in a vacuum oven overnight to obtain a modified graphene material.
[0062] S2, dissolving tea polyphenols in an organic solvent, preferably ethanol, then adding the modified graphene material in S1, stirring for 1-3 hours, preferably 2 hours, then high-speed centrifuging, washing with deionized water, and freeze-drying to obtain a tea polyphenol-modified graphene composite material.
[0063] In an optional embodiment, the epoxy resin is an aqueous epoxy resin dispersion. In essence, the epoxy resin is prepared by a non-ionic emulsifier through a phase inversion method and has good stability, low viscosity, and fine emulsion particles.
[0064] In an optional embodiment, the epoxy resin is an aqueous epoxy emulsion with a main chain segment grafted with a multi-secondary amino group, wherein the secondary amino group can react with the isocyanate in the topcoat (polyurethane coating) component before the epoxy group in the epoxy primer to form polyurea, which can reduce the occurrence of side reactions in the wet-to-wet contact between the primer and topcoat while forming a uniform and dense coating with the topcoat, thereby improving the appearance and performance of the matching paint film.
[0065] In an optional embodiment, the epoxy value of the epoxy resin is 450-550 mol / 100 g, the pH value is 7.5-8.5, the solid content is 50-55%, and the particle size is 0.8-1.0 μm.
[0066] In an optional embodiment, the epoxy resin is selected from epoxy resins of model XS0402 (with grafted polyamine groups) and XS0402 CI (without grafted polyamine groups) provided by Honghui Company, or epoxy resins of model EPIKOTE TM One or more of the epoxy resins of Resin 6529.
[0067] In an optional embodiment, the pigment filler is selected from one or more of titanium dioxide, talc, feldspar powder, precipitated barium sulfate, and mica powder.
[0068] In an optional embodiment, the additive includes one or more of a dispersant, a defoamer, a leveling agent, a rheological additive, and an anti-flash rust agent; in particular, by weight, the additive preferably includes 0.5-1.5 parts of a dispersant, 0.1-1 parts of a defoamer, 0.1-1 parts of a preservative, and 0.1-1 parts of a leveling agent.
[0069] In an optional embodiment, the dispersant is one or more of polycarboxylic acid sodium salt, polyacrylate potassium salt, and polyacrylate sodium salt.
[0070] In an optional embodiment, the defoaming agent is a high-carbon alcohol defoaming agent or a silicone defoaming agent.
[0071] In an optional embodiment, the preservative is one or more of aluminum dihydrogen tripolyphosphate, zinc phosphate, and zinc hydroxyphosphite.
[0072] In an optional embodiment, the leveling agent is a polyether siloxane copolymer.
[0073] In an optional embodiment, the water-based curing agent is a water-based epoxyamine curing agent, with an active hydrogen equivalent of 140 g / mol (solid basis) and a solid content of 80%. Preferably, the water-based epoxyamine curing agent is an aqueous solution of a polyamide-modified alicyclic polyamine adduct.
[0074] In an optional embodiment, the water-based curing agent is selected from the water-based curing agent model XS0608C provided by Honghui Company.
[0075] The third aspect of the present application provides a corrosion-resistant coating obtained by the preparation method of the corrosion-resistant coating as described above.
[0076] The above implementation is described in more detail below in conjunction with specific examples.
[0077] Example 1
[0078] The corrosion-resistant coating in this example was prepared according to the formulation in Table 1 below.
[0079] Table 1
[0080]
[0081] The preparation method thereof is as follows:
[0082] Stir component A thoroughly and evenly, then stir component B thoroughly and evenly and heat to 60°C, then mix component A and component B and stir evenly until cooled to room temperature, wherein the mass ratio of component A to component B is 6:1.
[0083] Wherein, the tea polyphenol-modified graphene composite material is prepared by the following method:
[0084] S1. Dissolve graphene in water, then perform ultrasound for 1.5 hours until the graphene is evenly dispersed in the water, then add urea, wherein the mass ratio of urea to graphene is 5:1, stir the obtained liquid phase and reflux at 80°C for 1 hour, finally wash the mixture with deionized water for multiple times, and dry it in a vacuum oven overnight to obtain a modified graphene material.
[0085] S2, dissolving tea polyphenols in an organic solvent, preferably ethanol, and then adding the modified graphene material in S1, stirring for 2 hours, then high-speed centrifuging, washing with deionized water, and freeze-drying to obtain a tea polyphenol-modified graphene composite material.
[0086] Example 2
[0087] Compared with Example 1, most of them are the same, except for the replacement of the target component, as shown in Table 2 below.
[0088] Table 2
[0089]
[0090] Example 3
[0091] Compared with Example 1, most of them are the same, except for the replacement of the target component, as shown in Table 3 below.
[0092] Table 3
[0093]
[0094]
[0095] Example 4
[0096] Compared with Example 1, most of them are the same, except for the replacement of the target component, as shown in Table 4 below.
[0097] Table 4
[0098]
[0099] Example 5
[0100] Compared with Example 1, most of them are the same, except for the replacement of the target component, as shown in Table 5 below.
[0101] Table 5
[0102]
[0103]
[0104] Example 6
[0105] Compared with Example 1, most of the contents are the same except for the replacement of the target component, as shown in Table 6 below.
[0106] Table 6
[0107]
[0108] Comparative Example 1
[0109] Compared with Example 1, most of them are the same, except for the replacement of the target component, as shown in Table 7 below.
[0110] Table 7
[0111]
[0112]
[0113] Comparative Example 2
[0114] Compared with Example 1, most of them are the same, except for the replacement of the target component, as shown in Table 8 below.
[0115] Table 8
[0116]
[0117] Comparative Example 3
[0118] Compared with Example 1, most of them are the same, except for the replacement of the target component, as shown in Table 9 below.
[0119] Table 9
[0120]
[0121] Test Case
[0122] 1. The coatings prepared in Examples 1-6 and Comparative Examples 1-3 were coated on the surface of a 1mm thick low-carbon steel plate, left to stand for 48 hours to form a coating, and the water absorption rate and bonding strength were tested after immersion in water for 24 hours according to DL / T693-1999;
[0123] 3. Acid resistance: According to GB / T 1763-1979, soak for 120h at 23±2℃, no blistering, wrinkling or color spot, slight gloss loss and discoloration are allowed.
[0124] 4. Alkali resistance: According to GB / T 1763-1979, soak for 720h at 23±2℃, no blistering, wrinkling or color spot, slight gloss loss and discoloration are allowed.
[0125] 5. Salt spray resistance: According to GB / T 1771-2007, 600h (the rust width on one side of the scratch is ≤2mm, and there are no bubbles, rust or shedding on the other board surfaces 5mm away from the scratch.)
[0126] 6. Corrosion resistance: Soak in 50% sulfuric acid at 80℃ for 15 days. If there is no crack, blister or peeling, it is qualified. Soak in 50% sulfuric acid at 80℃ for 20 days. If there is no crack, blister or peeling, it is better. Soak in 50% sulfuric acid at 80℃ for 25 days. If there is no crack, blister or peeling, it is excellent.
[0127] The test results are shown in Table 10 below.
[0128] Table 10
[0129] Test items Water absorption Bond strength Acid resistance Alkali resistance Salt spray resistant Corrosion resistance Example 1 0.09 6.1 excellent excellent excellent excellent Example 2 0.07 6.0 excellent excellent excellent excellent Example 3 0.07 6.2 excellent excellent excellent excellent Example 4 0.08 5.9 excellent excellent excellent excellent Example 5 0.07 6.3 excellent excellent excellent excellent Example 6 0.08 5.9 excellent excellent excellent excellent Comparative Example 1 0.19 4.1 qualified qualified qualified qualified Comparative Example 2 0.26 2.1 qualified qualified qualified qualified Comparative Example 3 0.21 3.8 qualified qualified qualified qualified
[0130] As can be seen from the above table, the coatings obtained in Examples 1 to 6 of the present application are significantly better than those in Comparative Examples 1 to 3 in various aspects when applied to metal coatings. Furthermore, the coatings obtained in the present application have the characteristics of low water absorption, strong adhesion, and excellent acid resistance, alkali resistance, salt spray resistance, and corrosion resistance when applied to metal coatings.
[0131] In Comparative Example 1, the main problem is that the unmodified graphene is not compatible with the coating. In Example 1 of the present application, the amino group of urea reacts with the carboxyl groups distributed on the surface of graphene to form ammonium carboxylate, thereby successfully grafting the amino group onto the graphene, making the surface of the graphene looser and rougher, making the graphene more dispersed in the organic coating and reducing the possibility of agglomeration, thereby improving the corrosion resistance of the coating. In addition, the tea polyphenol molecule contains multiple phenolic hydroxyl groups, which can form hydrogen bonds with the carboxyl groups on the surface of graphene to further enhance the dispersion ability of the graphene. Conversely, the antioxidant effect of tea polyphenols prevents the natural weathering and oxidation of the coating, and further prevents the entry of corrosive media. The synergistic effect of the two improves the corrosion resistance of the coating.
[0132] In Comparative Example 2, no filler was added, or in Comparative Example 3, ordinary filler was added. The brittleness and micropores formed during the evaporation of the solvent in the coating formed the coating, resulting in poor coating performance.
[0133] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A corrosion-resistant coating, characterized in that: It includes component A and component B; In parts by weight, component A includes 40-60 parts of epoxy resin, 20-40 parts of pigments and fillers, 1-5 parts of additives, and 10-50 parts of deionized water; component B includes 40-60 parts of water-based curing agent, 1-5 parts of tea polyphenol-modified graphene composite material, and 30-50 parts of deionized water; The mass ratio of component A to component B is (4-7):
1.
2. A corrosion-resistant coating according to claim 1, characterized in that: The tea polyphenol-modified graphene composite material is prepared by the following method: S1. Dissolve graphene in water, perform ultrasonic treatment for 1-2h until the graphene is evenly dispersed in the water, then add urea, the mass ratio of urea to graphene is 4-6:1, stir and reflux at 60-100°C for 0.5-1.5h, wash and dry to obtain a modified graphene material; S2, dissolving tea polyphenols in an organic solvent, then adding the modified graphene material in S1, stirring for 1-3 hours, centrifuging, washing, and freeze-drying to obtain a tea polyphenol-modified graphene composite material.
3. A corrosion-resistant coating according to claim 1 or 2, characterized in that: The epoxy resin has an epoxy value of 450-550 mol / 100 g, a pH value of 7.5-8.5, a solid content of 50-55%, and a particle size of 0.8-1.0 μm; And / or, the pigments and fillers are selected from one or more of titanium dioxide, talc, feldspar powder, precipitated barium sulfate, and mica powder; And / or, the water-based curing agent is a water-based epoxyamine curing agent.
4. A corrosion-resistant coating according to claim 1 or 2, characterized in that: The auxiliary agent includes 0.5-1.5 parts of dispersant, 0.1-1 parts of defoamer, 0.1-1 parts of preservative, and 0.1-1 parts of leveling agent.
5. A corrosion-resistant coating according to claim 5, characterized in that: The dispersant is one or more of polycarboxylic acid sodium salt, polyacrylate potassium salt, and polyacrylate sodium salt; And / or, the defoamer is a higher alcohol defoamer or an organosilicon defoamer; And / or, the preservative is one or more of aluminum dihydrogen tripolyphosphate, zinc phosphate, and zinc hydroxyphosphite; And / or, the leveling agent is a polyether siloxane copolymer.
6. A method for preparing a corrosion-resistant coating, characterized in that: The steps include: Stir component A thoroughly and uniformly, then stir component B thoroughly and uniformly and heat to 50-80°C, preferably 60°C, and then mix and stir component A and component B until cooled to room temperature, wherein the mass ratio of component A to component B is 4-7:1; Among them, component A includes 40-60 parts of epoxy resin, 20-40 parts of pigments and fillers, 1-5 parts of additives, and 10-50 parts of deionized water; component B includes 40-60 parts of water-based curing agent, 1-5 parts of tea polyphenol-modified graphene composite material, and 30-50 parts of deionized water.
7. The method for preparing a corrosion-resistant coating according to claim 7, characterized in that: The tea polyphenol-modified graphene composite material is prepared by the following method: S1. Dissolve graphene in water, perform ultrasonic treatment for 1-2h until the graphene is evenly dispersed in the water, then add urea, the mass ratio of urea to graphene is 4-6:1, stir and reflux at 60-100°C for 0.5-1.5h, wash and dry to obtain a modified graphene material. S2, dissolving tea polyphenols in an organic solvent, then adding the modified graphene material in S1, stirring for 1-3 hours, centrifuging, washing, and freeze-drying to obtain a tea polyphenol-modified graphene composite material.
8. A method for preparing a corrosion-resistant coating according to claim 7 or 8, characterized in that: The epoxy resin has an epoxy value of 450-550 mol / 100 g, a pH value of 7.5-8.5, a solid content of 50-55%, and a particle size of 0.8-1.0 μm; And / or, the pigments and fillers are selected from one or more of titanium dioxide, talc, feldspar powder, precipitated barium sulfate, and mica powder; And / or, the water-based curing agent is a water-based epoxyamine curing agent; And / or, the auxiliary agent includes 0.5-1.5 parts of dispersant, 0.1-1 parts of defoamer, 0.1-1 parts of preservative, and 0.1-1 parts of leveling agent.
9. A corrosion-resistant coating obtained by the method for preparing the corrosion-resistant coating as described in any one of claims 7 to 9.
Citation Information
Patent Citations
Self-repairing waterborne polyurethane anticorrosive coating and preparation method thereof
CN113831825A
Outdoor steel structure anti-corrosion coating and preparation method thereof
CN118562380A
Anticorrosive composite coating material with self-repairing function and preparation method for coating
CN110564266A
Antibacterial, antioxidant and flame-retardant water-based plastic-replacing oil as well as preparation method and application thereof
CN117106336A
High-performance wet-on-wet waterborne epoxy primer and preparation method thereof
CN117986958A
Cited By
Corrosion-resistant coating and preparation method thereof
CN120173476A